Meningkatkan Hasil Belajar IPA Materi Pengelompokan Benda Tunggal Dan Benda Campur Melalui Metode Eksperimen Siswa Kelas V SDIslamiyah 6 Kota Ternate - Apridayani Marasabessy (Peneliti.net, 2023)
This research is motivated by the existence of obstacles in the teaching and learning process in science learning at SD Islamiyah 6 Ternate City, among other things students are less active in learning, teachers have not used experimental methods in learning science. The purpose of this study was to determine the increase in science learning outcomes in the material for grouping single substances and mixed substances for fifth grade students of SD Islamiyah 6, Ternate City. This type of research is Classroom Action Research which consists of 4 stages, namely, planning, implementing action, observing and reflecting. This research was conducted in 2 cycles. The subjects in this study were class V with a total of 23 students, consisting of 7 girls and 16 boys. Data collection was carried out using observation sheets in the learning process, namely to find out the increase in the student learning process using test sheets to find out the increase in student learning outcomes and documentation. Based on the results of research conducted on student learning outcomes in cycle I, the class average score in cycle one was 6.41 with a completeness percentage of 34.78%, increasing in cycle II with an average score of 8.26 with a completeness percentage of 86.95 % While the results of teacher activities in cycle I amounted to 56.25% while in cycle II it increased to 88.88% while the results of observations of student activities namely in cycle one were 53.57% while in cycle II it increased to 82.14%. these results can illustrate that using the experimental method in learning science can improve student learning outcomes at SD Islamiyah 6 Ternate City.